(untitled) (Al-Academy, 2018)
Education varies in terms of form and content between verbal and abstract education through the delivery of knowledge and enriching experiences through verbal communication and ephemeral learning and based on sensory experiences that provide visual and audio visualizations that make it imperative to install and retain knowledge and experience. It is obvious that meanings And the concepts grow the more tangible sensory experiences that make the process of communication highly efficient, and the more the learner’s acquisition of direct sensory experiences, ie the first source is the life situations and normal circumstances of the process of communication, but if these can not be available It is necessary to adopt appropriate alternatives through which these positions can be provided in a way that allows the acquisition of sensory experiences or what is known as educational means, especially in educational situations caused by the use of alternatives to cause damage, including increasing knowledge and spatial and temporal barriers and size and the difficulty of communicating with real and dangerous situations and other situations Which is taken into account when teaching. It is possible to achieve fruitful learning, which depends on the clarity of the communication process. This process, which is heavily influenced by excessive verbalism, weak motivation, differences in knowledge between teacher and learner, The educational method is especially important in the art education classes and parallel to the most relevant lesson of the activities of the curriculum of art education. The work of implementing different teaching strategies that require the use of teaching aids related to the content. Where teaching is more attractive and can overcome the problem of large classes and shorten the amount of time and effort in the educational process. Scientific and technological progress and scientific and technological achievements produced by the communications revolution of materials and tools have had a great impact on education scientists in understanding the role of natural sciences in the use of these scientific techniques in education as new educational means. However, the use of these methods in a chaotic manner does not depend on methodology, the study sought to identify the educational methods prevailing in the primary schools for the academic year 2017/2018. The research came out with the most important findings and conclusions. It emphasizes the use of teaching aids of all kinds, Creativity among primary school students